2017
DOI: 10.22631/ijaep.v6i2.88
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prolonged Periods Classroom Settings in Intra-abdominal fat area and its Consequence on Posture/Balance Control among Algerian Childhood College Preparatory School.

Abstract: Abstract:The play has been shown to help children adjust to the school setting and to enhance children's learning [1]. Since this theory, the current study was designed to examine the significance of mechanical effects of intra-abdominal on posture/balance control among the Algerian Childhood Primary Schools. Since our teachers emphasise the good classroom settings as a discipline pedagogical aspect of success learning. While High- Based on the differences acquired by the research team, we emphasise that prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…As guidelines to structure the optional and recommended classroom-based physical activity. Reports via this study as a requested frequency and time physical activity policy to build the recommended Primary School Active Break Program, able to overall energy expenditure (Mohammed, Z, 2017), sitting time and cardio-metabolic outcomes (Mantzaria, et al, 2019). Compared to 15 min assured by Primary active break programs studies (Glapa, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As guidelines to structure the optional and recommended classroom-based physical activity. Reports via this study as a requested frequency and time physical activity policy to build the recommended Primary School Active Break Program, able to overall energy expenditure (Mohammed, Z, 2017), sitting time and cardio-metabolic outcomes (Mantzaria, et al, 2019). Compared to 15 min assured by Primary active break programs studies (Glapa, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Implicated in the present study to predict the optional intervention period and intensity that can meet the recommended 60 minutes of moderate-to vigorousintensity physical activity daily (Hills, et al, 2015). More suitable in the case of school environments to improve child health status, functional abilities and sitting time adjustment that surpasses 6 hours pre-day in our primary schools (Mohammed, Z, 2017). Reported in similarities as a risk factor for various negative health outcomes like obesity, blood pressure, high blood sugar, excess body fat around the waist and abnormal cholesterol levels that make up metabolic syndrome.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, existed evidences showed female adolescents are at higher risk compared with male adolescents regarding this health [2] . It has been discussed that physical inactivity [1,3] , unhealthy posture during daily activity [4,5] , prolonged improper backpack loading during the childhood years and carrying the bag in one side of body [4] are influent behavioral risk factors for back pain among adolescents. It has been revealed that three main psychological factors including Behavioral Capability (knowledge and skills to perform a given behavior); Self-Efficacy (SE); and Outcome Expectation Beliefs (behavioral beliefs) could predict any behavior changes [6] .…”
Section: Introductionmentioning
confidence: 99%
“…It is on the rise among adolescent and pupils' population and the prevalence varies between 11% and 52.1%, and is associated with back pain in adulthood [2][3][4][5]. Behavioral risk factors for back pain in children are, among others, prolonged improper backpack loading during the childhood years, carrying the bag in one side of body [1,[5][6][7], physical inactivity [1,8], and improper posture during daily activity [7,9]. Thus it is argued that in order to prevent or reduce burden of back pain in pupils, theory-based back care educational programs for this population are of prime importance [10].…”
Section: Introductionmentioning
confidence: 99%